2023
DOI: 10.1017/s0033291723000491
|View full text |Cite
|
Sign up to set email alerts
|

A practical risk calculator for suicidal behavior among transitioning U.S. Army soldiers: results from the Study to Assess Risk and Resilience in Servicemembers-Longitudinal Study (STARRS-LS)

Abstract: Background Risk of suicide-related behaviors is elevated among military personnel transitioning to civilian life. An earlier report showed that high-risk U.S. Army soldiers could be identified shortly before this transition with a machine learning model that included predictors from administrative systems, self-report surveys, and geospatial data. Based on this result, a Veterans Affairs and Army initiative was launched to evaluate a suicide-prevention intervention for high-risk transitioning soldiers. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Another participant noted high rates of suicide attempts in the five years following separation. Indeed, research indicates that suicide risk is 2.5 times higher for veterans in the first year following separation relative to those who are still in the military, and a study on U.S. Army veterans found that 1 percent of veterans attempt suicide in the first year post-discharge (Geraci et al, undated;Kearns et al, 2023;Shen, Cunha, and Williams, 2016). Although risk decreases over time, one study identified that suicide risk remained high even six years after separation (Shen, Cunha, and Williams, 2016).…”
Section: Fulfillment Of Basic Needsmentioning
confidence: 99%
“…Another participant noted high rates of suicide attempts in the five years following separation. Indeed, research indicates that suicide risk is 2.5 times higher for veterans in the first year following separation relative to those who are still in the military, and a study on U.S. Army veterans found that 1 percent of veterans attempt suicide in the first year post-discharge (Geraci et al, undated;Kearns et al, 2023;Shen, Cunha, and Williams, 2016). Although risk decreases over time, one study identified that suicide risk remained high even six years after separation (Shen, Cunha, and Williams, 2016).…”
Section: Fulfillment Of Basic Needsmentioning
confidence: 99%
“…It is likely that attending the required and universal DoD Transition Assistance Program (U.S. Department of Defense, 2022) might be sufficient to assist many low-risk TSMVs in their transition to civilian life. However, TSMVs identified as high-risk by a practical risk calculator for suicidal behavior, based on the STARRS-LS model (Kearns et al, 2023), would most likely benefit from individualized and intensive interventions that consisted of community programs, a certified sponsor, and streamlined access to VA healthcare, including case management, primary care, and suicide-safety planning group treatment (Geraci, Borah, et al, 2023;Goodman et al, 2021).…”
Section: Stepped-care Interventions Based On Risk Levelsmentioning
confidence: 99%
“…[13][14][15][16] All service members have been shown to have lower risk when they are focused on a clear mission such as during deployment, yet they experience a higher risk during the postdeployment adjustment period, and this risk increase continues into retirement. [17][18][19] US service members have contact with primary care practitioners in the month before suicide more than half the time. [20][21][22] Primary care practitioners seek tools to aid in identifying at-risk patients whom they otherwise may miss.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand factors that might increase suicide risk in the military, numerous studies have analyzed protective and risk factors for service members . All service members have been shown to have lower risk when they are focused on a clear mission such as during deployment, yet they experience a higher risk during the postdeployment adjustment period, and this risk increase continues into retirement …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation